Folie à Deux in the Setting of COVID-19 Quarantine - Maxsaya Baez Nuñez; Ezequiel Rodriguez; Matthew DeLuca; Krishan Chirimunj; Monica Dhingra (Case Reports in Psychiatry)
We relay the case of a middle-aged male and his mother, an elderly female, who presented with folie à deux in the context of shared delusions of persecution and somatization during the COVID-19 quarantine period. The delusions were described as electric microwave shocks being transmitted to their internal organs by neighbors, followed by somatic symptoms of palpitations, headaches, and a shock-like perception. To the best of our knowledge, there have not been any reports that describe the development of folie à deux in the setting of the COVID-19 quarantine. Folie à deux may be defined as delusions affecting two or more individuals, usually first-degree relatives. Delusions classically transmit from one person, coined the inducer, to one or several individuals, the induced, who share and may expand on the communicated delusions. The preconditions that must exist for folie à deux to develop are an intimate emotional association between the inducer and the induced and a genetic predisposition to psychosis, such as blood relations with primary relatives. Isolation from society has also been considered a potential risk factor for shared psychosis in the recent literature. Given that to the best of our knowledge, there have not been any reports describing the development of folie à deux in the setting of the COVID-19 quarantine, the authors aim to dissect how extended periods of shared isolation from society during such a significant time in history may have served as a significant precipitating factor in the onset of shared psychotic disorder, while simultaneously illustrating a parallel relation to how such conditions may predispose certain subgroups to similarly dynamic-based mental health disorders. In addition, an evaluation of the origins and multifactorial etiology of folie à deux, along with that of existing treatment modalities, and the emphasis on advancement toward more effective treatment approaches will be provided.